(untitled) (Eureka Journal of Humanities and Social Research, 2026)
Purpose: This article examines the historical formation, developmental characteristics, and strategic directions of free economic and industrial zones (FEZs) in Uzbekistan through historical-empirical analysis. The Navoi, Jizzakh and Angren FEZs were comprehensively studied in terms of reforms implemented from 2008 to 2024. Methods: The study employed historical-comparative analysis, chronological sequencing, and statistical data analysis. Primary sources included Presidential Decrees, State Statistics Committee reports, and over 90 scholarly publications. Results: By end-2022, Uzbekistan operated 37 FEZs and 296 small industrial zones, absorbing total investments of 2.6 billion. The Jizzakh FEZ produced 4,426.2 billion soums worth of goods from 2015 to 2021; Angren FEZ exports grew 95-fold from 2013 to 2017. Novelty: For the first time, a comparative historical analysis of three zones was conducted, empirically substantiating the effectiveness of the tax incentive system and identifying infrastructure constraints. Conclusions: Free economic zones are confirmed as a primary structural reform instrument for Uzbekistan’s economic modernization.